CIRCUMVENTION CHALLENGES IN THE WAKE OF TRUMP’S TARIFF POLICIES: INDONESIA’S STRATEGIC RESPONSES - Reza Pahlevi Chairul; Fuji Anrina (KANUN:JURNAL ILMU HUKUM, 2025)
In the absence of a multilateral World Trade Organization (WTO) framework to regulate circumvention, many countries have pursued unilateral remedies by enacting domestic laws and applying anti-circumvention measures to imported goods. Circumvention, evading duties, undermines the effectiveness of trade remedy instruments designed to protect domestic industries from unfair practices and import surges. Anti-circumvention regulations are complex and vary among major WTO members, creating significant enforcement challenges. These challenges have become especially acute amid global trade uncertainty driven by tariff measures during the United State of America under president Trump administration, underscoring the urgent need for enhanced policy dialogue, particularly regarding Indonesian interests. This article identifies key challenges facing Indonesia and proposes strategic responses. Using a normative legal approach, it highlights the rising number of anti-circumvention investigations by the United States of America (USA), the European Union (EU)’s broadened measures to include investment in developing countries, and unilateral actions by trading partners. It also examines the growing risks for Indonesian domestic producers due to circumvention activities. The article recommends to fostering discussions on circumvention issues in multilateral, regional, and bilateral fora; strengthening cooperation with international authorities; reinforcing the domestic regulatory framework to address fraudulent practices such as transshipment and weak customs enforcement; and finally promoting proactive cooperation from Indonesian companies during anti-circumvention investigations. These steps can protect Indonesian industries, bolster policy coherence, and contribute to a more predictable global trading environment.